Commercial banking : the management of risk - Fraser, Donald R. (South-Western College, 2001)
This book is divided into five parts: Introduction; Asset/Liability management: Controlling Interest rate risks; Balance sheet management: Risks and returns; Financial analysis; and Loan portfolio management.